Meta-analysis of the Mexican education system: Evolution and challenges - Torres, Arturo González; Hernández, María Luisa Pereira; Echeagaray, Melissa Edith Salazar; Castillo, Alba Marlene Chan (Edelweiss Applied Science and Technology, 2025)
The study analyzes the evolution of the Mexican educational system between 2018 and 2024, considering government reforms and their alignment with the United Nations Sustainable Development Goals. A Systematic Literature Review (SLR) was conducted in eight stages, using specific selection criteria focused on education, equity, and public policy. The main findings highlight five key factors: overall educational progress, the adoption of updated pedagogical approaches, the adaptation of policies to local contexts, the formation of academic groups to evaluate reforms, and the design of educational materials. Statistical analysis confirmed the relevance of these elements. The study concludes that transforming the system requires inclusive and context-sensitive policies, with the participation of various social actors. Practical implications include strengthening teacher training, adapting successful international models, and promoting interdisciplinary research to address current educational challenges.